Analyzing the Influence of Problem-Based Learning on Collaborative Skills: Evidence of a Large Effect Size - Arifin, Moh. Samsul; Antika, Linda Tri (Indonesian Journal of Biology Education, 2025)
Collaboration skills are essential competencies emphasized in the Merdeka Curriculum as part of the gotong royong dimension in the Pancasila Student Profile. However, observations at an Islamic boarding school-based senior high school in Madura indicated that students' collaboration skills were still low due to the dominance of teacher-centered learning. This study aimed to examine the effect of the Problem-Based Learning (PBL) model on the collaboration skills of tenth-grade students in biology learning. A quantitative approach was used with a quasi-experimental design involving a non-equivalent control group. The participants consisted of 62 students, divided into an experimental group (n = 32) that received PBL treatment and a control group (n = 30) that received direct instruction. Data on collaboration skills were collected using an observation sheet adapted from Hermawan, Widodo, and Saputra (2017), covering aspects such as contribution, time management, problem-solving, teamwork, and inquiry. The results of the Mann–Whitney U test showed a significant difference between the groups (U = 26.500, Z = –6.456, p < .001), with the experimental group achieving a higher median score (15.00) than the control group (10.00). The effect size was 1.60, indicating a significant effect. These findings demonstrate that PBL is effective in enhancing students' collaboration skills through active learning processes, and it is recommended for broader implementation in Islamic boarding school-based schools to support 21st-century education goals.